Bricks, sand, and marble : U.S. Army Corps of Engineers construct ion in the Mediterranean and Middle East, 1947-1991 - Grathwol, Robert P., 1939-; Moorhus, Donita M., 1942-; Center of Military History; United States. Army. Corps of Engineers (Washington, D.C. : Center of Military History, Corps of Engineers , U.S. Army : [For sale by the Supt. of Docs., U.S. G.P.O.], 2009)
Synopsis: The work of the U.S. Army Corps of Engineers in military c onstruction in the Mediterranean Basin and the Middle East created the infrastructure that made the U.S. policies of deterrence and containmen t possible. This work included not only construction in support of the U.S. Army and U.S. Air Force in these areas but also work executed on behalf of Middle East allies paid for with funds they provided. This b ook traces the activities of American military engineers from the recon struction that began in Greece after World War II through the construct ion of air bases in North Africa, the massive building program in Saudi Arabia, and support for the liberation of Kuwait in 1991. The history provides a background of the present role and position of the United S tates in that vital region.
Part 3: Army Engineers In Saudi Arabia, 1972-1988 -- 9: New progra ms and organizational changes, 1972-1977 -- Burgeoning workload -- Cont inuing work, 1972-1975 -- Saudi ordnance corps program -- Questions con cerning the role of corps -- Contonments at Khamis Mushayt and Tabuk -- Third cantonment -- New medical center and general hospital for the mi nistry of defense and aviation -- Other projects for the ministry of de fense and aviation -- Funding the projects -- Emergency water system re pair in Jiddah -- Transition to the Middle East division -- Handling th e growing volume of materials -- Staffing for the expanding workload -- Reorganizing engineering responsbilities -- Implementing the move to S audi Arabia -- Locating the division rear in Virginia -- New staff in B erryville -- Middle East division's initial years -- New districts -- E ngineer logistics command -- 10: Programs for the Ministry of defense and aviation in the 1970s and 1980s -- Upgrading Khamis Mushayt and Tab uk -- Medical support facilities -- Schools -- Area comander's headquat ers -- VIP complexes and family housing -- Providing the infrastructure -- Closing out the projects -- Peace Hawk and Peace Sun -- Headquarter s complexes -- Royal Saudi air force headquarters complex -- Ministry o f defense and aviaiton headquarters complex -- Executive office buildin g -- Design and construction of the headquarters complex -- Officiers c lub in Riyadh -- Designing medical centers -- 11: Modernization of the Saudi Arabian Navy and National Guard -- Saudi naval expansion program -- Initiating the program -- Ports at Jiddah and Jubayl -- Headquarter s of the Royal Saudi naval forces -- Naval program constrained -- Moder nizing the Saudi Arabian national guard -- Design phase -- Headquarter complex -- Military cities at Al Qasim and Al Hasa -- Construction phas e -- Training facilities at Khash, al An -- Request for a camel racetra ck -- Building the headquarters -- Ground settlement problems -- 12: K ing Abdulaziz military academy -- Beginning construction -- Procuring e quipment, furniture, and furnishings -- Getting the program on track, 1 981-1983 -- Completing the academy -- 13: King Khalid military city -- New master plan -- Cost-plus-award-fee contracting -- Preparing a cost -plus-award-fee contract -- Finding the right contractor -- Progress at Ras al Mishab -- Organizing for the construction -- Mobilization of th e Morrison-Knudsen Saudi Arabia consortium -- Responsibilities of the M orrison-Knudsen Saudi Arabia consortium -- Life support -- Construction support -- Management assistance and support -- Supervising the Morris on-Knudsen Saudi Arabia consortium -- Controversy over management -- CS -squared -- Tensions over management decisions -- Implications for prog ress -- Network analysis system -- Shortcoming of the Morrison-Knudsen Saudi Arabia consortium -- Allegations of corruption -- Ending the cost -plus-award-fee contract -- Completing King Khalid military city -- Pac kaging construction tasks -- Pace of construction, 1981-1983 -- Facing crises in funding -- Completing first brigade facilities, 1984 -- Part 4: Changing Geopolitics In The Middle East -- New US policy -- Adjusti ng the work in Saudi Arabia -- Iran-Iraq war -- Collapse of bipolar geo politics -- Iraq's attack on Kuwait -- 14: Reorienting the engineer ef fort, 1981-1986 -- Middle East division in the region -- Jordan -- Oman -- Design for the Oman program -- Masirah Island construction -- Khasa b -- Seeb -- Thamarit -- Program status in Oman by the mid-1980s -- Kuw ait -- Bahrain -- Egypt -- Sudan -- Other occasional work -- Refocusing the organization, 1981-1986 -- Extending the engineer assistance agree ment -- Adjusting staff size -- Managing work from forward and rear -- Relocating command authority -- 15: From division to Middle East/Afric a projects office, 1985-1991 -- Transition to the Middle East/Africa pr ojects office -- Agruments for division status -- Status of projects in December 1985 -- Adjusting to a new entity -- Ordnance program divisio n -- Closing out the Saudi program under the Middle East/Africa project s office -- Projects throughout the region -- Oman -- Kuwait -- Bahrain -- Egypt -- Sudan -- Voice of America -- Africa civic action -- Depart ment of defense dependent schools -- Status at the end of the decade -- Major administrative actions, 1986-1991 -- Lifecycle project managemen t -- Rethinking the future of the Middle East/Africa projects office -- International events intervene -- Transatlantic division -- Typing up loose ends -- Coming full circle -- Conclusion: Army engineers overseas : challenges, opportunities, and changing times -- Bibliography -- Abbr eviations -- Index.
Includes bibliographical references and index.
Also available via the internet from the GPO Access web site.
Keywords: United States. -- Army. -- Corps of Engineers -- History -- 20th cen tury; Military engineering -- Mediterranean Region -- History -- 20th cent ury; Military engineering -- Middle East -- History -- 20th century; Military architecture -- Mediterranean Region -- History -- 20th cen tury; Military architecture -- Middle East -- History -- 20th century; United States -- Military relations -- Mediterranean Region; United States -- Military relations -- Middle East; Mediterranean Region -- Military relations -- United States; Middle East -- Military relations -- United States